ESTILOS DE VIDA Y FORMAS DE PREVENCION DE LAS COMPLICACIONES DE LOS PACIENTES DIABETICOS TIPO II QUE ACUDEN AL SUBCENTRO DE SALUD DE LA PARROQUIA MALACATOS 2012- 2013 - Muñoz Curay, Lucia Margarita (2016)
The present work of STYLES OF LIFE AND FORMS OF PREVENTION OF THE COMPLICATIONS OF THE PATIENTS DIABETIC TYPE 2 THAT MALACATOS GOES TO THE SUBCENTRO OF HEALTH OF THE PARISH 2012 - 2013 are carried out it, with the purpose of proposing in a plan of Intervention guided to diminish the complications in the patients diabetic type 2 guided to the Families and community in general. The outlined objectives; to characterize the lifestyles in the diabetic users that go to the Sub Center of Health of Malacatos to present an intervention proposal that contributes from a combined way to prevent and/or to retard the complications in the users affected by this illness. Leaving of this objective intended: " To base the relating ones that allow to contribute to the education process and active communication of the collective fellows of the Parish Malacatos to improve the healthy lifestyles theoretically and you form of preventing complications, the patients that suffer diabetes mellitus type 2 starting from the focus of the community auto desarrollo give; cocktail with the methodology ESCAVIRIS.; to Identify the lifestyles of the users affected by the Diabetes Type II that you/they go to SC of Health of Malacatos; To establish the most frequent complications in the diagnosed patients of Diabetes type 2; To propose in a plan of Intervention guided to diminish the complications in the patients diabetic type 2 The fellows that participated went patient that went to the consultation, of the Sub Center of Health of the Parish Malacatos, diagnosed with DM2 by their medical dealers. The deterioration of the quality of life was measured with the scale of quality of life related with the health (ESCAVIRS), in its validated version and standardized to Spanish. The dependent variable was the evaluation of the index of deterioration of the quality of life estimated through ESCAVIRS. The independent variables understood the 5 time of evolution of the degenerative chronic condition of the DMTII of the selected patients, as well as some aspects sociodemográficos. The results revealed that 23% of the sample studied with some grade of deterioration in its quality of life in the evaluated areas. The interaction areas stand out with the team of health, the emotional and physical aspects. They have more risk for deterioration those patients with more than five years of evolution of the DMTII, educational level under and age bigger than 50 years. You concludes that the grade of deterioration of the quality of life in this type of patients is progressive and it is associated to the degenerative evolution of the illness.